Existential Contributions to the Problematization of Trauma: An Expression of the Bewildering Ambiguity of Human Existence (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper explores the problematization of trauma through the reductionist assumptions embedded within the medical model. A more holistic and flexible understanding is offered from an existential-phenomenological perspective, repositioning trauma as a potential crisis that bares the bewildering uncertainty and fragility of human existence. Implications for therapeutic practice are emphasised.
Keywords: Trauma; crisis; uncertainty; existentialism; phenomenology; Counselling Psychology; therapy